INTEGRATION OF GREEN ECONOMY PRINCIPLES IN THE REGIONAL SUSTAINABLE DEVELOPMENT OF SMALL BUSINESS ACTIVITIES (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article examines the significance of integrating green economy principles into the sustainable regional development of small businesses. It focuses on the rational use of natural resources, improvement of energy efficiency, implementation of environmentally friendly technologies, and reduction of the environmental impact of production processes. The article further explains that business activities based on green principles can enhance regional economic stability, create new employment opportunities, and strengthen the competitiveness of local markets. It concludes that combining environmental responsibility with economic effectiveness is a crucial factor in the modernization and long-term development of small enterprises.